Characteristics of the angled printed dipole array antenna with different numbers of dipole elements - Wang, Heesu; Park, Ikmo (Journal of Electromagnetic Engineering and Science, 2020)
This paper investigated the characteristics of series-fed angled dipole antennas as the number of dipoles increased from one to two, four, and eight. A parallel strip line printed on both sides of the substrate was used to connect angled printed dipoles of the same size in a series with equal spacing. As expected, although the gain increased as the number of dipoles increased, the impedance and gain bandwidths decreased. In addition, as the number of dipoles increased, the half-power beamwidth (HPBW) differences between the xz-and yzplanes decreased and the radiation pattern of the xz-plane became more symmetric. Antennas with one, two, four, and eight-dipole elements in a series were designed, and their peak gains were 5.0 dBi, 7.2 dBi, 9.4 dBi, and 10.4 dBi, respectively. The differences between the xz-and yz-plane HPBWs of the four antennas were 160.4°, 41.7°, 14.2°, and 5.3°, respectively. As the number of dipoles in the antenna increased, the differences between the HPBWs in the xz-and yz-planes decreased.
Keywords: 5G antenna; Dipole array; Endfire antenna; Ka-band; Millimeter-wave antenna; Printed dipole antenna